(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Zika, an emerging Aedes-mosquito-borne virus are currently being identified with alarming outbreak is spreading throughout the America. Health expert warn that anytime virus could enter Bangladesh due to worldwide easy communication of the people. Concerns have grown even stronger in Bangladesh after news media in Thailand and Taiwan reported cases of the viral infection among locals. Both places are popular destinations for Bangladeshi travellers, increasing the risk of the virus also spreading here. Aedes aegypti, the carrier of the virus, is also responsible for spreading dengue fever throughout the Indian sub-continent region, especially in Bangladesh and India. Pregnant women are at increased risk of neonatal complication like microcephaly if infected with ZIKA virus. This review describes epidemiology, transmission of ZIKAV, clinical presentation and recommendations for pregnancy according to CDC, RCOG,SGOC and WHO guidelines. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 40-45